Higher Order Bivariate Bell-Based Apostol-Frobenius-Type Poly-Genocchi Polynomials with Parameters a and b (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we unveil a novel category of Frobenius-Genocchi polynomials, grounded in the Bell numbers and Apostol-type functions. Our exploration delves into a comprehensive examination of these polynomials, elucidating various properties. Employing diverse analytical methods and leveraging generating functions for Bell-based Apostol-Frobenius-Type poly-Genocchi polynomials of higher order, we derive explicit and implicit summation formulas, complemented by their symmetric identities.
Keywords: Genocchi polynomials; Bell polynomials; Apostol-Frobenius- Type poly-Genocchi polynomials; Bell-based Apostol-Frobenius-Type poly-Genocchi polynomials; Stirling numbers